2021
DOI: 10.1530/edm-20-0211
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary metastasis unveiling a lung adenocarcinoma

Abstract: Summary Pituitary metastasis (PM) can be the initial presentation of an otherwise unknown malignancy. As PM has no clinical or radiological pathognomonic features, diagnosis is challenging. The authors describe the case of a symptomatic PM that revealed a primary lung adenocarcinoma. A 62-year-old woman with multiple sclerosis and no history of malignancy, incidentally presented with a diffusely enlarged and homogeneously enhancing pituitary gland associated with stalk enlargement. Clinical and biochemical eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Even though PM tends to occur in patients with known metastatic cancer, symptomatic pituitary metastases may be the initial presentation of an unknown malignancy. 6 In a case series of 157 cases of PM in Japan, 10.8% detection of pituitary metastasis was initial to diagnosing the primary lesion. 7 Different reports found that most cases of PM preceding the diagnosis of malignancy originated from lung cancers, as is for our case.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even though PM tends to occur in patients with known metastatic cancer, symptomatic pituitary metastases may be the initial presentation of an unknown malignancy. 6 In a case series of 157 cases of PM in Japan, 10.8% detection of pituitary metastasis was initial to diagnosing the primary lesion. 7 Different reports found that most cases of PM preceding the diagnosis of malignancy originated from lung cancers, as is for our case.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Different reports found that most cases of PM preceding the diagnosis of malignancy originated from lung cancers, as is for our case. 6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations